2000
DOI: 10.1115/1.1331057
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dynamic Friction Models for Simulation of One-Dimensional and Two-Dimensional Stick-Slip Motion

Abstract: In many mechanical systems, the tendency of sliding components to intermittently stick and slip leads to undesirable performance, vibration, and control behaviors. Computer simulations of mechanical systems with friction are difficult because of the strongly nonlinear behavior of the friction force near zero sliding velocity. In this paper, two improved friction models are proposed. One model is based on the force-balance method and the other model uses a spring-damper during sticking. The models are tested on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Karnopp has used the relation of the dynamic friction force during the slip phase formulated by Coulomb [42]. However, the friction force during the stick phase has been determined on basis of the equilibrium of forces.…”
Section: The Network Model and The Pspice Codementioning
confidence: 99%
“…Karnopp has used the relation of the dynamic friction force during the slip phase formulated by Coulomb [42]. However, the friction force during the stick phase has been determined on basis of the equilibrium of forces.…”
Section: The Network Model and The Pspice Codementioning
confidence: 99%
“…In this paper, the Tariku and Rogers model is modified and used to model the sticking and sliding behavior of smart devices on an underlying moving surface. The model is validated by comparing its behavior to experimentally measured data.…”
Section: Motivation and Introductionmentioning
confidence: 99%
“…Experimentation with various numbers of steps showed that 20 sub-steps produces reasonable answers. To address the second problem, a new criterion is proposed to distribute the friction force using a modification of Tariku and Roger's assumption [5]. The original model proposed by Tariku and Roger [5] assumes that a block accelerates in the direction of the inertial force regardless of its previous velocity direction in the micro-slip region.…”
Section: Proposed Two Dimensional Friction Modelmentioning
confidence: 99%
“…To address the second problem, a new criterion is proposed to distribute the friction force using a modification of Tariku and Roger's assumption [5]. The original model proposed by Tariku and Roger [5] assumes that a block accelerates in the direction of the inertial force regardless of its previous velocity direction in the micro-slip region. They considered the micro-slip region to be that where the magnitude of the sliding velocity is less than 0.1 mm/s [5].…”
Section: Proposed Two Dimensional Friction Modelmentioning
confidence: 99%
See 1 more Smart Citation